Analysis Environmental And State Losses In Corruption Offences - Frans, Mardian Putra; Sari, Agustina Indah Intan; Eldillon, Iddo (JURNAL HUKUM SEHASEN, 2025)
This research aims to discuss legal issues regarding the validity of environmental damage as an element of state loss in corruption crimes. The main objective of this research is to answer the legal issue of whether environmental damage can be categorized as an element of state loss in corruption crimes. The type of research used in this study is normative legal research, namely by examining legislation, legal doctrines, and legal principles related to the problems studied. The results show that environmental damage cannot be categorized as state losses as referred to in Article 2 paragraph (1) and Article 3 of the Anti-Corruption Law because the aquo article must be proven by the existence of real state financial losses, not potential or estimated state financial losses. Now, law enforcement must be able to prove the value of real or actual losses to state finances or the state economy (actual loss), not only based on the value of losses that may occur (potential loss).